The Influence of Family Economic Education on Consumptive Behavior of Students - Siska Anggraini; Depi Pramika; Riswan Aradea (Universitas Negeri Semarang, 2023)
This study aims to analyze the effect of economic education in the family on the consumptive behavior of SMA PUSRI Palembang students. This type of research is quantitative. Data collection techniques used were questionnaires, interviews and documentation. The sample technique in this study used simple random sampling with 86 students of class XI SMA PUSRI Palembang. The results of research on economic education in the family are 83% in the very strong category. The results of the analysis of consumptive behavior are 49% in the medium category. The results of hypothesis testing show that tcount>table=4.352>1.988 with a significance level of 0.00<0.05 which indicates that there is an effect of economic education in the family on students' consumptive behavior. With the results of a simple regression test, the variable economic education in the family has the ability of 18.4% to explain its effect on the dependent variable, namely consumptive behavior, while the remaining 81.6% is influenced by other variables.